Effect of algal organic matter on adsorption of glyphosate using coconut shell-activated carbon - Sufia Hena; Krishnat Shankar Patil; Nadia Leinecker; Tejas Bhatelia; Milinkumar Shah (Chemical Engineering Journal Advances)
Glyphosate contamination in water bodies poses a serious risk to human health and the environment; hence, its removal from water is a prospect of the highest priority. Adsorption using activated carbon has been extensively studied for glyphosate removal from water. However, surface water contains natural organic matter which can deteriorate activated carbon's adsorption capacity and selectivity for glyphosate. The current study investigates the effect of algal organic matter (AOM) on the adsorption of glyphosate on coconut shell-activated carbon (CSAC). At a set of experimental conditions using water with only glyphosate contamination, the equilibrium adsorption capacity was found to be 30.79 mg/g at an optimum pH of 3; and the equilibrium data could be represented by the Langmuir isotherm with a maximum uptake capacity of 48.3 mg/g. When experiments were repeated using water simultaneously contaminated with glyphosate and AOM (2 mg/L) at the same conditions, the adsorption capacity drastically decreased to 13.93 mg/g. It was observed that the type of AOM, whether it had higher polysaccharides (from the early growth phase of Chlorella vulgaris) or protein (from 40-day old culture), had a significant impact on glyphosate adsorption. The data suggest that CSAS selectivity for glyphosate is highly sensitive to pH. The regeneration experiments revealed 93 % glyphosate recovery when pH was further reduced to 1.5. Overall, the current study quantifies the decrease in CSAC's selectivity for glyphosate due to the presence of AOM and provides optimum pH for maximum selectivity and regeneration.